Spectrophotometric Properties of Geologically Young Regions on Ceres - Jian-Yang Li; Xiao-Duan Zou; Scott C. Mest; Stefan E. Schröder; Stefano Mottola; Jeffrey S. Kargel (2022)
Introduction: Results from the Dawn mission showed us an aqueously altered cryovolcanic world of Ceres, maybe a relict Ocean World [1, 2]. Geological studies suggested brine-driven features, including the cryovolcanic dome Ahuna Mons [3] and the Cerealia and Vinalia Faculae, which are carbonate- and chloride-rich evaporites [4] formed from brine extrusion with evidence of recent activity [5]. In addition, the Haulani crater is among the youngest impact features on Ceres [6], potentially excavating relatively fresh, volatile-rich subsurface materials with distinctly bright and blue spectral characteristics [7]. In this study, we focus on the spectrophotometric properties of the geologically young features, aiming to characterize Ceres’s regolith evolution and better understand the cryovolcanic processes. Here we report the preliminary results of the Haulani crater (latitude  -3º to 14º, longitude 0º to 20º) and Ahuna Mons regions (latitude -17º to -3º, longitude 308º - 322º). Data: We used the multiband images of Ceres collected by the Dawn Framing Camera with pixel scales <150 m/pixel and calibrated them to radiance factor (RADF) following [8, 9], including infield straylight removal for all color images. The scattering backplanes were calculated with the USGS ISIS software using the high-resolution digital terrain models from the Planetary Data System [10].  The alignment between the backplanes and the corresponding images was checked and adjusted. For each region, we defined four regions of interest (ROIs; Fig. 1) based on the geological context. Our photometric modeling was performed independently for each ROI in each of the seven color filters. <img src="data:image/png;base64, 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